Injuries in female elite athletes in rowing: A 1-year prospective epidemiological study - Park, K. J.; Kim, H. C.; Kim, Y. R. (Journal of International Academy of Physical Therapy Research, 2018)
This epidemiological study aims to determine the incidence, areas, severity, and time of occurrence of sports injuries in elite female rowing athletes who were training at the Jincheon National Training Center for a 1-year period from January 1st to December 31st, 2017. According to the daily injury reports form of the IOC, sport events, weight division, injured area, and cause of injury were recorded, and the following results were found. Upon comparing the incidence of sports injuries, there was a significant difference in weight of double scull athletes. In terms of sports, there was a significant difference between pair and athletes who played double skull. Injuries occurred most commonly in the lower extremity (40.5%), followed by the trunk (35.1%), upper extremity (24.3%). for all athletes in rowing. The knee and lumbar spine/lower back were the most common injury sites. More than 60% of all injuries were Level III, and injuries occurred most frequently during training, followed by weight training and then competition.